MAYBE We consider the system theBenchmark. Alphabet: 0 : [] --> a rec : [] --> (b -> (a -> c) -> a -> c) -> c -> a -> c s : [] --> b -> b Rules: rec f (g 0) => g rec f (g (s x)) => f x (rec f (g x)) Using the transformations described in [Kop11], this system can be brought in a form without leading free variables in the left-hand side, and where the left-hand side of a variable is always a functional term or application headed by a functional term. We now transform the resulting AFS into an AFSM by replacing all free variables by meta-variables (with arity 0). This leads to the following AFSM: Alphabet: 0 : [] --> a rec : [b -> (a -> c) -> a -> c * c] --> a -> c s : [b] --> b ~AP1 : [a -> c * a] --> c ~AP2 : [b -> c * b] --> c Rules: rec(F, ~AP1(G, 0)) => G rec(F, ~AP2(G, s(X))) => F X rec(F, ~AP2(G, X)) ~AP1(F, X) => F X ~AP2(F, X) => F X +++ Citations +++ [Kop11] C. Kop. Simplifying Algebraic Functional Systems. In Proceedings of CAI 2011, volume 6742 of LNCS. 201--215, Springer, 2011.